Toxicology as a diagnostic tool to identify the misuse of drugs in the perinatal period - Jones, Joseph (Frontiers in Pediatrics, 2023)
The use, misuse, and abuse of substances are a continued public health concern in this country and around the world. Perinatal exposure to substances of abuse is associated with a number of long-term negative consequences for the neonate. Resources to assist perinatal health professionals on this very complex subject are limited. The purpose of this document is to provide additional information with regard to selecting monitoring protocols, the specifics of appropriate testing methodologies, and the interpretation of toxicological findings. Understanding these concepts better allows perinatal healthcare professionals to be a voice for the voiceless in order to protect and enrich lives during this unprecedented opioid epidemic.